Pengenalan Investasi Melalui Simulasi Permainan Pasar Modal Sebagai Salah Satu Media Praktek Investasi di SMK MHS Batam - Wargadalam, Winanda Wahana; Aprayuda, Riyadi; Dzulfiqar, Mohamad Aif; Dinuka, Vina Kholisa; Gunawan, Hendra; Zainuddin, Muhammad; Tiara, Tiara; Soraya, Iassa Marcelina (Politeknik Negeri Batam, 2024)
High school students need to improve. Students in Batam, especially at the high school level, need to be equipped with sufficient knowledge to start investing, but an appropriate method is needed in conveying investment material because the age limit for trying to invest is 17 years while the age of high school students is not yet sufficient, so a method is needed. Another way to recognize investment from a young age is through practical games. Practicing investment games through capital market game simulations as one of the investment practice media for the early stages of Gen-Z through middle school students can be used as a practical tool where learning while playing is very popular with young people, especially Gen-Z. In implementing this community service, the method of implementing community service is divided into 3 stages, namely Pre-Field, Field, and Post-Field. This service activity is to increase the financial literacy of MHS Vocational School students and provide a better understanding of the capital market and investment from an early age. The success of this activity will provide sustainable benefits for MHS Batam Vocational School, with the availability of capital market simulation games as a means of increasing the financial literacy of students and teachers. This can help overcome the problem of low levels of financial literacy in society.